Concrete Creep Analysis Method Based on a Long-Term Test of Prestressed Concrete Beam - Mingfang Yang; Song Jin; Jinxin Gong (Advances in Civil Engineering)
Concrete creep plays a significant role in the long-term performance of the prestressed concrete structure. However, most of the existing prediction models cannot accurately reflect the in-site concrete creep in a bridge construction environment. To improve the prediction accuracy of creep effects in concrete structures, an innovative creep analysis method is developed in this study. Parameters in the creep model in fib MC 2010 have been calibrated with respect to the long-term loading test results of the prestressed concrete beam. The measured strains of concrete and the midspan deflections of the test beam are compared with the predicted results using the creep model in fib MC 2010. It indicates that the results predicted by the calibrated creep model are in good agreement with the test results. However, the results predicted by the creep model in fib MC 2010 significantly deviate from the test results. This proposed creep analysis method can provide a new thought to improve the predicted effect of the creep effects on creep-sensitive structures.